Reaction of mung (Vigna radiata L. Wilczek) genotypes to root-knot nematode, Meloidogyne javanica and M. incognita - Goel, S. R. (Annals of Agricultural Research, 2014)
Forty-three genotypes of mung were evaluated for their reaction to root-knot nematode, M.Â Â incognita and M. javanica. Results revealed that one genotype TM-96-1 (BARC) was resistant while five other genotypes were moderately resistant to M. javanica aginst M. incognitanone was found to be resistant while ten other genotypes were moderately resistant to M. incognita. Rest of the genotypes were either susceptible or highly susceptible to root-knot nematodes, M. javanica and M. incognita.